Quality of Chronic Care Statistically Mediates the Association Between eHealth Literacy and Self-Management Among Adults with Diabetes in a Shared Care Model - Jinmei Su; Jing Cui; Xia Wang; Zhitian Cao; Mengchi Li; Ying Pang; Wei Cui; Wenhui Jiang; Ting Huang (Healthcare, 2026)
Background/Objectives: As a lifelong chronic condition, diabetes requires self-management, which plays an essential role in slowing disease progression and improving treatment outcomes. This research aimed to investigate whether the quality of chronic care statistically mediates the relationship between eHealth literacy and self-management among adults with diabetes participating in a shared care model. Methods: A cross-sectional design along with convenience sampling was utilized in this study. From March 2025 to March 2026, 332 individuals with diabetes were enrolled from a shared care model at a tertiary hospital in northwestern China. The participants completed the Chinese versions of the three validated instruments, and the data were processed using SPSS 27.0 and PROCESS 4.1. Results: Significant positive correlations were found among the three core variables (all p < 0.01). The mediation model confirmed that the quality of chronic care acted as a partial and statistically significant mediating role in the relationship between eHealth literacy and self-management among adults with diabetes (β = 0.146, 95% CI: 0.114–0.398). Conclusions: This study found that patients with diabetes participating in the shared care model reported relatively favorable self-management capabilities. eHealth literacy was indirectly associated with self-management behaviors through the quality of chronic care. However, given the cross-sectional design of this study, these findings should be interpreted as statistical associations rather than causal evidence, and reverse causality cannot be ruled out. Future longitudinal studies are needed to establish temporal ordering and causal relationships among these variables.